Ultra high speed full adder for biomedical applications - Basavoju Harish; M. S. S. Rukmini (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
In the field of bio medical engineering high performance CPU for digital signal processing plays a significant role. Frequency efficient circuit is a paramount requirement for the portable digital devices employing various digital processors. In this work a novel high speed one-bit 10T full adder with complemented output was described. The circuit was constructed with XOR gates which were built using two CMOS transistors. The XOR gate was constructed using 2T multiplexer circuit style. It was observed that power consumption of the designed circuit at 180nm with supply voltage 1.8V is 183.6 uW and delay was 1.809 ps whereas power consumption at 90nm with supply voltage 1.2V is 25.74 uW and delay was 8.245 ps. The observed Power Delay Product (PDP) in 180nm (at supply voltage 1.8V) is 0.33 and in 90nm (at supply voltage 1.2V) is 0.212. The work was extended by implementing a 32-bit Ripple Carry Adder (RCA) and was found that the delay at 180nm is 93.7ps and at 90nm is 198ps. The results were drawn at 180nm and also 90nm technology using CAD tool. The results say that the present work offered significant enhancement in speed and PDP compared with existing designs.